EFEKTIFITAS PENGGUNAAN MEDIA PETA KONSEP UNTUK MENINGKATKAN PRESTASI BELAJAR AKUNTANSI - Wahyudin, Agus; Fithrona, Arina (Dinamika Pendidikan, 2007)
the objective of this study is to know the effectiveness of using concept map media to improve the success of learning accounting with the sub-topic is Classification of Account for XI students 1st semester in SMA Negeri 3 Pekalongan year 2005/2006. Population of the research was all XI students semester 1 SMA Negeri 3 Pekalongan year 2005/2006 with the numbers were 232 students divided into 6 classes. Sample was determined by simple random sampling technique, thus getting 2 classes as the samples, Class XI IPS 1 consisted of 39 students as the controlled class and class XI IPS 2 consisted of 37 students as the experimental class. Data was collected by documentation and experimental technique. And the instrument of collecting data was test. In this research, there are 2 data analysis. Those are pre data analysis to equalize the controlled and experimental groups by using normality test, equality test two variance and equality test two average, and the post step analysis to test hypothesis by t-test one right side. The result of t-test showed that the average of learning achievement of experimental group was better than controlled group. It can be concluded that the using of concept map as learning media sub-topic on classification account is more effective than the group without concept map media. From the result of study above, it is suggested that teachers and students can try to use concept map media in the process of accounting learning. Key words: Effectiveness, concept map media and achievement